Lowered ADCP data during Maria S. Merian cruise MSM89 - Karstensen, Johannes; Krahmann, Gerd (PANGAEA, 2023)
LADCP measurements used a two-instrument configuration with two Teledyne RDI 300 kHz workhorse ADCPs mounted in down- and up-looking positions. Data collection and processing was performed according to recommendations in the GO-SHIP manual (Thurnherr et al., 2010).